Pemanfaatan Karet Alam Untuk Produk Barang Jadi Di Desa Suban Jeriji Kecamatan Rambang Dangku Kabupaten Muara Enim - Abu Hasan; Robert Junaidi; KA Ridwan (Politeknik Negeri Sriwijaya, 2019)
Besides the domestic consumption of natural rubber into rubber goods is still very small, Indonesia is also still dependent on the export of these commodities abroad. The new natural rubber producing countries which are quite troubling the world natural rubber market including Indonesia are also China, Vietnam and Cambodia. One of the main weaknesses of Indonesian farmers' natural rubber is dirty. This is a cause of low prices. The cost of cleaning the rubber is too high. Therefore it is indeed necessary to have a way to diversify rubber products or increase the consumption of natural rubber in the country is very important. In order for many people to produce rubber goods, this means that many people know that cleaning rubber is necessary and does not need to be polluted. In Palembang itself, there was PT. Sri Bina Havea and Intirub Tire Factory, but both are gone. Thus, the way to produce rubber goods of natural rubber needs to be socialized to the Indonesian people, especially in South Sumatetra. This certainly greatly influences the development of the local economy given that South Sumatetra is the largest producer of natural rubber in Indonesia and this result is mostly produced by farmers rather than large companies. For this reason, this service aims to provide information about the technology of processing natural rubber into rubber goods to the public. This service was carried out on the people of Suban Jeriji village, Rambang Dangku Sub-District, Muara Enim Regency, South Sumatra. The method used in this activity is a lecture and interactive discussion about the manufacture of natural rubber finished goods with the help of LCD and accompanied by providing samples of finished goods products from semi-finished natural rubber. The target to be achieved in this activity is the formation of insights into thinking that natural rubber goods are a way to overcome the ever-uncertain prices of natural rubber on the market. The long-term target of this activity is perhaps one day there are students or students who are interested in becoming entrepreneurs of natural rubber goods.